PCB dechlorination hotspots and reductive dehalogenase genes in sediments from a contaminated wastewater lagoon - Mattes, Timothy E.; Ewald, Jessica M.; Liang, Yi; Martinez, Andres; Awad, Andrew; Richards, Patrick; Hornbuckle, Keri C.; Schnoor, Jerald L. (Environmental science and pollution research international, 2018)
Polychlorinated biphenyls (PCBs) are a class of persistent organic pollutants that are distributed worldwide. Although industrial PCB production has stopped, legacy contamination can be traced to several different commercial mixtures (e.g., Aroclors in the USA). Despite their persistence, PCBs are subject to naturally occurring biodegradation processes, although the microbes and enzymes involved are poorly understood. The biodegradation potential of PCB-contaminated sediments in a wastewater lagoon located in Virginia (USA) was studied. Total PCB concentrations in sediments ranged from 6.34 to 12,700 mg/kg. PCB congener profiles in sediment sample were similar to Aroclor 1248; however, PCB congener profiles at several locations showed evidence of dechlorination. The sediment microbial community structure varied among samples but was dominated by Proteobacteria and Firmicutes. The relative abundance of putative dechlorinating Chloroflexi (including Dehalococcoides sp.) was 0.01–0.19% among the sediment samples, with Dehalococcoides sp. representing 0.6–14.8% of this group. Other possible PCB dechlorinators present included the Clostridia and the Geobacteraceae . A PCR survey for potential PCB reductive dehalogenase genes (RDases) yielded 11 sequences related to RDase genes in PCB-respiring Dehalococcoides mccartyi strain CG5 and PCB-dechlorinating D. mccartyi strain CBDB1. This is the first study to retrieve potential PCB RDase genes from unenriched PCB-contaminated sediments.